High-resolution record of stable isotopes in soil carbonates reveals environmental dynamics in an arid region (central Iran) during the last 32 ka - Bayat, Omid; Karimi, Alireza; May, Jan-Hendrik; Fattahi, Morteza; Wiesenberg, Guido L. B.; Egli, Markus (Frontiers in Earth Science, 2023)
Although central Iran is pivotal for palaeoclimatic correlations, palaeoenvironmental data for this region is very sparse and a reliable chronology for pedogenic features is lacking. We therefore tried to answer the question how the environmental conditions and, in particular, the climate developed over time by using the isotopic signatures of pedogenic carbonates. We present a chronology of pedogenic carbonates in association with stable carbon and oxygen isotopes in both the matrix and coating carbonates of a relict palаeosol (Baharan palaeosol) in central Iran to understand the dynamics of environmental changes in this region during the late Quaternary. The palаeosol experienced several episodes of leaching during pedogenesis as reflected in its morphology (carbonate coatings under the rock fractions) and geochemical characteristics (Ba/Sr ratios). The δ18O values of both the matrix and coating carbonates in the upper 60 cm (especially in the upper 20 cm) of the pedon are enriched (∼4‰) compared to the subsoil and are mainly related to the impact of evaporation. Moreover, the δ13C values of the carbonates are in isotopic disequilibrium with the modern vegetation cover (desert shrubs) of the study area and are enriched in different degrees. The carbonates in the top 60 cm are formed by the input of atmospheric CO2 and calcareous dust while deeper carbonates formed in an environment exhibiting a higher contribution of C4 plants. Based on the radiocarbon chronology of carbonate coatings, it seems that three main stages of palaeoenvironmental changes occurred in the region during the last 32 ka. The first stage lasted ca. 5,000 years (between 31.6 and 26.0 ka) and was accompanied by deep leaching under sub-humid climatic conditions and the expansion of C4 plants. Under the dominance of semi-arid conditions during the second stage until the late Holocene, a gradual increase in the δ18O values and aridity occurred in the region. The last phase in the late Holocene was characterised by the establishment of an arid and evaporative environment with a sparse vegetation cover. A climatic correlation using the oxygen isotopic composition of secondary carbonates from the Baharan palaeosol, Soreq Cave (the Levant) and Hoti Cave (Oman; both having speleothems records) suggested a climatic connection between central Iran and the eastern Mediterranean during the late Pleistocene and between central Iran and northern Oman during the late Holocene.